Strategies For Strengthening the Economic Security of Business Entities in The Context of Global Financial And Economic Challenges - Тetyana CALINESCU; Ganna LIKHONOSOVA; Оlena ZELЕNKО; Serhii PIDMOHYLNYI (Communications of International Proceedings, 2022)
Each country mainly focuses on its legislation, which determines the indicators of national security. The main role in the development of the system of strengthening the economic security of business entities should be played by program-target and strategic methods aimed at achieving the national interests of the country in the face of global threats and formalized in the concept of national security. The purpose of the study is the theoretical and applied aspects of the strategy of strengthening the economic security of business entities in the context of global challenges of the global financial and economic system. Methods / approaches: research methodology is based on methods of statistical comparative analysis; logical and heuristic; extrapolation, graphic modeling. Result: in the course of the research the authors proposed a mechanism of self-strengthening of business entities in the conditions of deteriorating financial security; graphical interpretation of the proposed mechanism shows that the degree of spread of financial difficulties and the degree of sensitivity of economic entities to the shock they experience directly depends on the density of the network; with increasing connectivity, the possibility of absorbing shocks in the credit system due to the spread of risks through the network tends to zero; the proposed mechanism allows to adequately assess the situation with regard to financial and economic threats and to develop relevant strategic measures to eliminate them. Conclusions: being in a difficult financial situation, the entity, by default, will limit the amount of possible lending or set higher interest rates for its borrowers, adversely affecting their financial position (negative interaction); accordingly, the decline in financial stability is spreading throughout the financial and credit network, this phenomenon becomes a channel for the emergence and spread of financial difficulties of all involved in the financial and economic system of economic entities. Strategic directions for strengthening the economic security of business entities should be: improving the institutional parameters of business; strengthening financial indicators both at the level of the country and at the level of the entities themselves; development of export potential of business entities; improving the investment environment of the business; providing scientific, technical and technological basis for the activities of business entities; strengthening the production component of economic security; strengthening the energy independence of business through the introduction of energy-saving technologies in production and management activities; improving the environmental level of production.
Keywords: economic security; financial and economic challenges; business entities; threat; crisis; stability.